Using antibiotics responsibly: are we there yet?. (August 2016) - Dyar, Oliver James; Obua, Celestino; Chandy, Sujith; Xiao, Yonghong; Stålsby Lundborg, Cecilia; Pulcini, Céline
Problems of antibiotic access and excess coexist in the world today and are compounded by rising rates of antibiotic resistance. We introduce two dimensions of responsibility to this context: responsible individual practices and a broad societal obligation centered on sustainability. Acting on these responsibilities requires recognizing the potential tensions between an individual optimum for antibiotic use and the societal optimum. We relate the tragedy of the commons metaphor to this situation to illustrate the complexity involved, and we draw on real-world experiences in Uganda, India, China and France. We conclude that we must form a global stewardship of antibiotics that can link access, innovation and conservation efforts across countries to ensure sustainable access to effective antibiotics for all who need them.